PERANCANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF TEMA SELAMATKAN MAKHLUK HIDUP PADA MATA PELAJARAN IPA KELAS VI BERBASIS ANDROID - Kolo, Yesualda Rogeria; Nababan, Darsono; Kelen, Yoseph P. K.; Baso, Budiman (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2023)
Technology is growing rapidly and has covered almost all areas of life, one of which is education. The learning process at Yaperna Tuamese Elementary School is still experiencing problems in providing learning media and dealing with students who are left behind in material due to illness or activities outside of school. The learning process only uses textbooks in front of the classroom with so few book packages, so students feel bored and lazy to study. So while the concentration on students must be directed specifically at science subjects. Through an Android-based interactive multimedia learning application, students can explore the material independently. The designed media includes text, images, audio, and video to help teachers prepare learning media and maintain students' attention and concentration on lessons. Rapid Application Development (RAD) with 4D mode is the configuration method used. Through the results that have been tested, users feel more interested and more easily understand material with interactive multimedia than those who are used to using textbooks.